Mastering Microsoft Dynamics 365 customer engagement : an advanced guide to developing and customizing CRM solutions to improve your business applications - Somani, Deepesh (Packt Publishing, 2019)
A comprehensive guide packed with the latest features of Dynamics 365 for customer relationship management Key Features Create efficient client-side apps and customized plugins that work seamlessly Learn best practices from field experience to use Dynamics 365 efficiently Unleash the power of Dynamics 365 to maximize your organization's profits Book Description Microsoft Dynamics 365 is an all-in-one business management solution that's easy to use and adapt. It helps you connect your finances, sales, service, and operations to streamline business processes, improve customer interactions, and enable growth. This book gives you all the information you need to become an expert in MS Dynamics 365. This book starts with a brief overview of the functional features of Dynamics 365. You will learn how to create Word and Excel templates using CRM data to enable customized data analysis for your organization. This book helps you understand how to use Dynamics 365 as an XRM Framework, gain a deep understanding of client-side scripting in Dynamics 365, and create client-side applications using JavaScript and the Web API. In addition to this, you will discover how to customize Dynamics 365, and quickly move on to grasp the app structure, which helps you customize Dynamics 365 better. You will also learn how Dynamics 365 can be seamlessly embedded into various productivity tools to customize them for machine learning and contextual guidance. By the end of this book, you will have mastered utilizing Dynamics 365 features through real-world scenarios. What you will learn Manage various divisions of your organization using Dynamics 365 customizations Explore the XRM Framework and leverage its features Provide an enhanced mobile and tablet experience Develop client-side applications using JavaScript and the Web API Understand how to develop plugins and workflows using Dynamics 365 Explore solution framework improvements and new field types Who this book is for Mastering Microsoft Dynamics 365 Customer Engagement is for you if you have knowledge of Dynamics CRM and want to utilize the latest features of Dynamics 365. This book is also for you if you're a skilled developer looking to move to the Microsoft stack to build business solution software. Extensive Dynamics CRM development experience will be beneficial to understand the concepts covered in this book.